2018
DOI: 10.5294/aqui.2018.18.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Use of a User-Friendly Tablet Application to Communicate with Pediatric Patients on Mechanical Ventilators

Abstract: Objetivos: examinar cómo el uso de una aplicación para tableta como ayuda en la comunicación con pacientes pediátricos con respirador artificial afecta el nivel de satisfacción con la comunicación por parte del personal de enfermería y en las díadas cuidador–paciente. Materiales y método: se utilizó el diseño pretest-postest de un solo grupo para analizar el nivel de satisfacción del personal de enfermería con la comunicación y se utilizó un diseño de grupo de control pretest-postest no equivalente para los cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Our development was supported by previous studies where tablets were used to assist communication. 17 The tablet's user-friendly design and adequate illustration of needs and feelings for communicating with this group of patients may be the reason why it can improve communication efficacy. The nursing staff's conclusion that the application was appropriate for use demonstrated its apparent support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our development was supported by previous studies where tablets were used to assist communication. 17 The tablet's user-friendly design and adequate illustration of needs and feelings for communicating with this group of patients may be the reason why it can improve communication efficacy. The nursing staff's conclusion that the application was appropriate for use demonstrated its apparent support.…”
Section: Discussionmentioning
confidence: 99%
“…16 Rarely have devices been provided to assist the patients with intubation in communicating their needs. 17 In practice, the nurses try to supply the devices that assist patients to communicate through writing on paper. In some instances, the patients attempt to write to express their needs, yet it has been observed that they cannot control their writing and deliver understandable messages.…”
Section: Introductionmentioning
confidence: 99%